2019
DOI: 10.1016/j.molmet.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and lifestyle related factors influencing whole blood metabolite levels – A comparative analysis of three large cohorts

Abstract: ObjectiveHuman blood metabolites are influenced by a number of lifestyle and environmental factors. Identification of these factors and the proper quantification of their relevance provides insights into human biological and metabolic disease processes, is key for standardized translation of metabolite biomarkers into clinical applications, and is a prerequisite for comparability of data between studies. However, so far only limited data exist from large and well-phenotyped human cohorts and current methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…However, our study revealed large heterogeneity of serum metabolomes that resulted in low accuracy of classification models based on specific metabolites. This heterogeneity could result from various lifestyle-related factors, a phenomenon that was addressed in recent large metabolomics studies [ 40 , 41 ]. This aspect was not addressed specifically in the current study, yet putative lifestyle-related differences between populations (represented by Polish and Italian cohorts in our study) reduced the accuracy of serum metabolome-based signatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study revealed large heterogeneity of serum metabolomes that resulted in low accuracy of classification models based on specific metabolites. This heterogeneity could result from various lifestyle-related factors, a phenomenon that was addressed in recent large metabolomics studies [ 40 , 41 ]. This aspect was not addressed specifically in the current study, yet putative lifestyle-related differences between populations (represented by Polish and Italian cohorts in our study) reduced the accuracy of serum metabolome-based signatures.…”
Section: Discussionmentioning
confidence: 99%
“…From an initial 62 metabolites, 30 passed quality control criteria for further analysis (Table S7). Furthermore, to stabilize the analyses, outliers were removed by applying a cutoff of ±5 standard deviations based on the mean of the logarithmized nonzero data [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other metabolite sets previously reported to be associated with IS within 24 hours after symptom onset, 14–18 our set showed the highest accuracy for separating patients with IS from patients with SMs and NCs in our samples. Differences in diagnostic accuracies and in the sets of circulating metabolites may be routed in (1) different recruitment strategies resulting in sample differences with regard to age, sex, comorbidities, and medication, which are known to influence circulating metabolite levels 33 ; (2) different metabolomic profiling approaches (untargeted vs targeted) and technologies (eg, nuclear magnetic resonance spectroscopy vs mass spectrometry); (3) small sample sizes resulting in insufficient statistical power to capture true differences of hundreds of measured metabolites; (4) lack of a validation step; and (5) lack of statistical adjustments for potential confounders and multiple testing. Among 11 metabolites that overlapped between previously published studies and our discovery analysis after adjusting for age and sex (“basic model,” stage 1), only 4 also met the prespecified criteria for statistical significance after adjustment for additional confounders (“full model”) and were validated in an independent sample (stage 2).…”
Section: Discussionmentioning
confidence: 99%